STRATEGI THINK TALK WRITE TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Jimayanti, Berliana; Sugiyono, Sugiyono; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to analyze the influence of think talk write application on students' learning outcomes in Social Science learning in the fifth grade SDN 33 Pontianak Utara. The method used is experiment with Quasi Experimental design form Nonequivalent Control Group Design. Population and sample in this research is all fifth grader of SDN 33 Pontianak Utara consisting of two classes that is, class five A and  B which amounts to 56 students. Data collection techniques used are measurement and the instruments is  multiple choice test. Based on data analysis, the result of experimental class average posttest is 75,66 and posttest of control class is 67,00, thitung  is 2,35 and ttabel is 1,6749, because thitung  > ttabel, Ha is accepted. It can be concluded that there is the influence of think talk write application on students' learning outcomes in Social Science learning in the fifth grade SDN 33 Pontianak Utara. Based on the calculation of effect size is 0,58, which includes medium criteria, that is 0,58 > 0,8. Thus, it can be said that the implementation of think talk write has a positive effect on students' learning outcomes in Social Science learning in the fifth grade SDN 33 Pontianak Utara. Key Word : Influence, Think Talk Write, Learning Outcomes, Social Science.